Signal Transducer and Activator of Transcription 3 Hyperactivation Associates With Follicular Helper T Cell Differentiation and Disease Activity in Rheumatoid Arthritis - Deng, Jun; Fan, Chaofan; Gao, Xin; Zeng, Qunxiong; Guo, Ruru; Wei, Yunbo; Chen, Zhian; Chen, Yanan; Gong, Dongcheng; Feng, Jia; Xia, Yan; Xiang, Shifei; et al. (Frontiers in Immunology, 2018)
Follicular helper T (Tfh) cells are the specialised CD4+ T cell subset that supports B cells to produce high-affinity antibodies and generate humoral memory. Not only is the function of Tfh cells instrumental to mount protect antibodies, but also to support autoantibody production and promote systemic inflammation in autoimmune diseases. However, it remains unclear how the activation of Tfh cells is driven in autoimmune diseases. Here we report that in patients with rheumatoid arthritis (RA), excessive generation of CXCR5+PD-1+ memory Tfh cells was observed and the frequency of memory Tfh cells correlated with disease activity score calculator for RA (DAS28). The differentiation of Tfh cells is dependent on signal transducer and activator of transcription 3 (STAT3), the key transcription factor downstream of cytokine signal pathways. A drastic increase of phosphorylated STAT3 (pSTAT3) in CD4+ T cells were detected in RA patients who also produced larger amounts of STAT3-stimulating cytokines including IL-6, IL-21, IL-10 and leptin than those of healthy controls. Importantly, the phosphorylation status of STAT3 in CD4+ T cells positively correlated with the plasma concentration of IL-6 and the frequency of memory Tfh cells. This study reveals an IL-6-pSTAT3-Tfh immunoregulatory axis in the pathogenesis of RA and reinforces its candidature as biomarkers and targets for diagnosis and therapy.